Representasi Kesetaraan Gender Pada Iklan Pil Kb Andalan Versi Dapur Di Televisi - Muhammad Abdul Ghani; Rohmiati (Jurnal ISIP: Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
This article reports on the results of research on the representation of gender equality in advertising and the meaning that is built around Andalan family planning pill products. The advertisement in question is the Kitchen Version of the aforementioned pill products on the television, examined and discussed using Roland Barthes’s semiotic analysis method. An interview with the Creative Director of the advertisement also contributes to the findings of this research. The results of the study illustrate that gender equality in a family is represented by the participation of the husband in various activities in the kitchen with his wife, the division of domestic work, and a dialogue that gives women the agency to make the decision to postpone pregnancy. The myth of the kitchen as an arena for women’s work has shifted to that in which even men can take part. The representation of gender equality and the depiction of a harmonious atmosphere between husband and wife as a happy family imply the association of birth control products to the provision of happiness with the increasingly equal role of women 8305-3. Mies. (2002). Negara dan Perempuan: Reflexi Atas Jurnalisme Gender Pada Masa Orba. Jakarta : Yayasan Jurnal Perempuan. Noviani, Ratna. (2002). Buku Jalan Tengah Memahami Iklan : Tata Realitas, Representasi dan Simulasi. Yogyakarta : Pustaka Pelajar. Shimp,T & Andrews,J. (2013). Advertising, Promotion, and other aspeccts of Integrated Marketing Communications. Ninth edition. Boulevard: South-Western Sobur, Alex. (2003) Surjadi, Erna. (2011). Gender Skateboard: Kekuatan Spirit Gender Dalam Rumah Tangga. Jakarta : Public Policy Forum Indonesia Sobur, Alex. (2013). Semiotik Komunikasi. Bandung : PT. Remaja Rosdakarya. Subandy, Idi & Suranto, H. (1998). Wanita Dan Media: Konstruksi Ideology Gender Dalam Ruang Public Orde Baru. Bandung : PT. Remaja Rosdakarya. Sugiyono. (2008). Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung : Alfabeta. Wolin, Lori D. (2003). Gender Issues in Advertising-an Oversight Synthetis of Research:1970-2002. Journal of Adertising Research. March 2003. DOI 10.1017/S002184990303012